Enhancing Students’ Environmental Care Character through the Application of “A Plate of Food” as a Learning Medium in Chemistry Education - Familia Novita Simanjuntak; Leony Sanga Lamsari Purba; Elferida Sormin; ST Fatimah Azzahra; Nova Irawati Simatupang; Putri Anjani; Lester E. Orpilla (Jurnal Pendidikan Sains Indonesia, 2026)
Chemistry education is not only oriented towards mastering scientific concepts, but also plays an important role in shaping students' character, particularly their environmental stewardship. This study aims to describe the improvement of students' environmental stewardship through the application of the "A Plate of Food" learning media in chemistry learning. This learning media links the concept of food chemistry with everyday environmental issues, such as food management, waste reduction, and sustainable consumption. This study used a qualitative descriptive method. The research subjects were 54 11th-grade students from Don Bosco High School, selected using a total sampling technique. Data collection was carried out through observation, interviews, and an environmental stewardship questionnaire. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The study's results indicate that using the "A Plate of Food" media in chemistry instruction can increase students' awareness of the importance of protecting the environment. This is reflected in changes in students' attitudes toward managing food waste, increased awareness of waste issues, and students' understanding of the relationship between chemical concepts and environmental issues. Therefore, the "A Plate of Food" learning medium can be an effective tool for strengthening environmental awareness in chemistry education. This research is expected to contribute to the development of innovative chemistry learning oriented toward character education and environmental sustainability